Governing Deepfakes: Legal Initiatives and Regulatory Gaps - Yousefi, Yasaman; Sánchez Galera, María Dolores; Tumminelli, Angelo; Caltagirone, Calogero; Tonello, Tommaso (Deepfakes, Democracy, and the Ethics of Synthetic Media: A Synthesis of the SOLARIS Project, 2026)
This chapter examines the pervasive threat of digital disinformation, with a specific focus on AI-generated content as a paradigmatic challenge to contemporary governance. The analysis blends ethical and legal perspectives to assess existing mitigation strategies. AIGC occupies a critical intersection of advanced technical capability, complex social meaning-making, and often conflicting legal protection frameworks. Consequently, effective responses require an interdisciplinary approach that integrates conceptual clarity, technical standards, robust legal instruments, and widespread social interventions to preserve public trust and protect vulnerable individuals.